Implan Koklea - Tandio, Aditya; Indrasworo, Dyah (RSUD Dr. Saiful Anwar Province of East Java, 2022)
The prevalence of sensorineural hearing loss was around 0.07% to 5.2% and increased with age. Cohlear implant was one of the modality to improve hearing function. Cochlear implant produce the electrical impulse needed for hearing. External sound was captured by the processor to be delivered to internal implant. In general, the implant was indicated for severe bilateral sensorineural hearing loss which cannot be improved with other hearing aids. The implantation procedure was relatively safe with minor and infrequent complication of vestibular disorder. The other complication was mostly iatrogenic. Despite the rare complication, the improvement of hearing and quality of life after the implantation depend on the patients, relatives and multidicsciplinary team. Cochlear implant was recommended for sensorineural hearing loss. Apart from the successful implantation, the hearing improvement tremendously depend on the patient, patients’ relatives and multidisciplinary team.